The influence of board structure and CEO duality On capital structure: evidence from sri Lankan Financial services industry - Nishanthan, K.; Naresh, K.; Niroshan, A. (University of Jaffna, 2014)
This paper investigates empirically the interaction between corporate governance mechanisms and capital structure of Sri Lankan financial service industry. Board size, Non executive director proportion and CEO/chair person Duality were taken as the variables of the board composition where as debt to equity ratio and debt ratio were taken as the measures of capital structure. The sample of the study is confined to the Bank, finance and insurance sector consists of 30 companies listed in the Colombo stock exchange over a period past 5 years from 2008 to 2012. We analyzed our data by employing descriptive statistics, Pearson correlation analysis and linear multiple regression to examine the nature and extent of the relationship between the variables and determine whether any cause and effect relationship between them. From the hypothesis test carried out, the results of the study not purely support the potential interaction between corporate governance variables and capital structure. The results provide additional insights into corporate governance practices in Sri Lanka. The present study is important in the sense that it empirically provides evidence for managers, investors and other decision makers that how much corporate governance practices have influence on capital structure. However, this study is subject to some limitations. Firstly, data only representing the period of five years of listed companies. Secondly, only three corporate governance variables were considered.
Keywords: Board Structure; CEO Duality; Capital Structure; Sri Lanka